Grainy Head in Wound Healing - Cristo, Inês Rodrigues Silva (2019)
"Epithelial wound healing is an inherent ability of all organisms to deal with aggressions from the surrounding environment and maintain tissue barrier integrity. Wounds can result from accidental trauma, surgery or various pathological conditions. Independently on the cause, all wounds need to be properly solved to avoid complications, ranging from infection to fibrosis and tumour initiation. Understanding the cellular and molecular basis of wound repair is an important asset for biomedical research. The process of wound healing is attained in a highly regulated and efficient manner to ensure correct return to homeostatic conditions.(...)"